2022
DOI: 10.1111/1348-0421.12982
|View full text |Cite
|
Sign up to set email alerts
|

Coccomyxa sp.KJ extract affects the fate of T cells stimulated by toxic shock syndrome toxin‐1, a superantigen secreted by Staphylococcus aureus

Abstract: T cell stimulation by bacterial superantigens induces a cytokine storm. After T cell activation and inflammatory cytokine secretion, regulatory T cells (Treg) are produced to suppress the immune response. Coccomyxa sp.KJ (IPOD FERM BP-22254), a green alga, is reported to regulate immune reactions. Therefore, we examined the effects of Coccomyxa sp.KJ extract (CE) on the superantigen-induced immune response. When human peripheral blood mononuclear cells (PBMCs) were stimulated with toxic shock syndrome-1 (TSST-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Consistent with our previous study [13], here we showed that both P and AS treatment decreased IL-2 and increased IL-17 expression. Conversely, IL-5 and IL-13 production decreased upon P and AS treatment, which differs from the results of our previous study [13].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our previous study [13], here we showed that both P and AS treatment decreased IL-2 and increased IL-17 expression. Conversely, IL-5 and IL-13 production decreased upon P and AS treatment, which differs from the results of our previous study [13].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our previous study [13], here we showed that both P and AS treatment decreased IL-2 and increased IL-17 expression. Conversely, IL-5 and IL-13 production decreased upon P and AS treatment, which differs from the results of our previous study [13]. This discrepancy between results could be because we used partially purified P and AS in this study, which may have depleted some Th2 cytokine-inducing factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recently, Ohshima et al reported that a water-soluble extract of Coccomyxa sp. KJ affected T-cell fates and helped ameliorate superantigen-induced T cell hyperactivation and immune suppression [20]. Alternatively, it is plausible that the therapeutic effects we observed may have been mediated, at least in part, by other algal components.…”
Section: Discussionmentioning
confidence: 85%